The Auburn conference : a novel - Piazza, Tom, 1955- (University of Iowa Press, 2023)
"It is 1883 and America is at a crossroads. The Civil War is nearly twenty years in the past, Reconstruction has been crushed in the South, and the Gilded Age is bringing unprecedented prosperity to some, along with radical social and class conflicts. At a tiny college in upstate New York, an idealistic young professor has managed to convince Mark Twain, Frederick Douglass, Herman Melville, Walt Whitman, Harriet Beecher Stowe, Confederate memoirist Forrest Taylor, and romance novelist Lucy Comstock to participate in the first (and last) Auburn Writers' Conference for a public discussion about the future of the nation. Over the course of a weekend this already combustible mix is heated up by a group of Suffragists advocating for women's rights, a contingent of die-hard Confederate sympathizers, an apocalyptic street-corner preacher, and a muckraking journalist who stirs the pot in hopes of bringing things to a boil. In this wildly audacious fictional tour de force, author Tom Piazza brings these figures to life as they encounter one another onstage and off - arguing, telling stories, reading aloud, and finally engaging in a debate that leads the gathering to the edge of chaos. By turns brilliantly comic and eerily prescient, The Auburn Conference vibrates with questions as alive and urgent today as they were in 1883 - the chronic American conundrums of race, class, and gender, and the fate of the democratic ideal"--